The therapeutics of arecoline - Murray, J. M. (My University, 1908)
Introduction: Arecoline (C8H13NO2) is the alkaloid or active principle of Areco catechu. Arecoline Hydrobromate (C8H13NO2HBr), the only preparation used in medicine, occurs in white crystals and is very soluble in water and alcohol. It is a diaphoretic, diuretic, and sialagogue and cathartic.
Citation: Murray, J. M. The therapeutics of arecoline. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Chemistry; Arecoline; Alkaloids; Drugs; Graduating theses; Senior theses; Theses